Continuous Anti-TNFα Use Throughout Pregnancy: Possible Complications For the Mother But Not for the Fetus. A Retrospective Cohort on the French National Health Insurance Database (EVASION). (November 2018) - Luu, Maxime; Benzenine, Eric; Doret, Muriel; Michiels, Christophe; Barkun, Alan; Degand, Thibault; Quantin, Catherine; Bardou, Marc
Abstract Objectives Inflammatory bowel diseases (IBD) need long-term treatment, which can influence pregnancies in young women. Uncontrolled IBD is associated with poor pregnancy outcomes. Despite the labeling of Anti-tumor necrosis factor (TNF) antibodies (anti-TNFα) which indicates that their use is not recommended during pregnancy, anti-TNFα are increasingly being used during pregnancy and may expose women and their fetuses to treatment-related complications. Existing recommendations on the timing of treatment during pregnancy are inconsistent. We aimed to assess the safety of anti-TNFα treatment in pregnant women with IBD, and up to the first year of life for their children. Methods An exposed/non exposed retrospective cohort was conducted on the French national health system database SNIIRAM (Système National d'Information Inter-Régimes de l'Assurance Maladie). All IBD women who became pregnant between 2011 and 2014 were included. Women with concomitant diseases potentially treated with anti-TNFα were excluded. Anti-TNFα exposure (infliximab, adalimumab, golimumab or certolizumab pegol) during pregnancy was retrieved from the exhaustive prescription database in SNIIRAM. The main judgment criterion was a composite outcome of disease-, treatment- and pregnancy-related complications during pregnancy for the mother, and infections during the first year of life for children. Results We analyzed data from 11, 275 pregnancies (8726 women with IBD), among which 1457 (12.9%) pregnancies were exposed to anti-TNFα, mainly infliximab or adalimumab, with 1313/7722 (17.0%) suffering from Crohn's disease and 144/3553 (4.1%) from ulcerative colitis. After adjusting for disease severity, steroid use, age, IBD type, and duration and concomitant 6-mercaptopurine use, anti-TNFα treatment was associated with a higher risk of overall maternal complications (adjusted Odds Ratio (aOR) = 1.49; 95% confidence interval (CI): 1.31–1.67) and infections (aOR = 1.31; 95% CI: 1.16–1.47). Maintaining anti-TNFα after 24 weeks did not increase the risk of maternal complication, but interrupting the anti-TNFα increased relapse risk. No increased risk for infection was found in children (aOR = 0.89; 95% CI: 0.76–1.05) born to mother exposed to anti-TNFα during pregnancy. Conclusions Anti-TNFα treatment during pregnancy increased the risk of maternal complications compared to unexposed; however, discontinuation before week 24 increased the risk of disease flare. There was no increased risk for children exposed to anti-TNFα up to 1 year of life.